Identification and Characterization of Thermostable Y-Family DNA Polymerases η, ι, κ and Rev1 From a Lower Eukaryote, Thermomyces lanuginosus - Vaisman, Alexandra; McDonald, John P.; Smith, Mallory R.; Aspelund, Sender L.; Evans, Thomas C.; Woodgate, Roger (Frontiers in Molecular Biosciences, 2021)
Y-family DNA polymerases (pols) consist of six phylogenetically separate subfamilies; two UmuC (polV) branches, DinB (polIV, Dpo4 pol), Rad30A/POLH (pol), and Rad30B/POLI (pol) and Rev1. Of these subfamilies, DinB orthologs are found in all three domains of life; eubacteria, archaea, and eukarya. UmuC orthologs are identified only in bacteria, whilst Rev1 and Rad30A/B orthologs are only detected in eukaryotes. Within eukaryotes, a wide array of evolutionary diversity exists. Humans possess all four Y-family pols (pols η, ι, κ, and Rev1), Schizosaccharomyces pombe has three Y-family pols (pols η, κ, and Rev1), and Saccharomyces cerevisiae only has polη and Rev1. Here, we report the cloning, expression, and biochemical characterization of the four Y-family pols from the a lower eukaryotic thermophilic fungi, Thermomyces lanuginosus. Apart from the expected increased thermostability of the T. lanuginosus Y-family pols, their major biochemical properties are very similar to properties of their human counterparts. In particular, both Rad30B homologs (T. lanuginosus and human polɩ) exhibit remarkably low fidelity during DNA synthesis that is template sequence dependent. It was previously hypothesized that higher organisms had acquired this property during eukaryotic evolution, but these observations imply that pol originated earlier than previously known, suggesting a critical cellular function in both lower and higher eukaryotes.